THE IMPACT OF UNANTICIPATED POLITICAL EVENTS ON STOCKS MARKET RETURNS: EMPIRICAL EVIDENCE FROM SAUDI ARABIA - Fodol, Mohamed Zakaria; Bin Abdul Aziz, Hassanuddeen (IJIBE (International Journal of Islamic Business Ethics), 2019)
Abstract:This study aims to identify the effect of unexpected political-events on Saudi stock market returns based on the efficient market hypothesis (EMH) assumptions.  The disappearance of the Saudi journalist Jamal Khashoggi in Turkey is the political event has been determined in this study.  The data collected from ten companies traded in the Saudi stock market which accounted for more than 62 percent of the total market capitalization. However, this paper applied the Event Study Methodology. The results showed that the Saudi stock market initially reacted to the event and tried to absorb the information received but could not correct itself in most of the window event period. It seems that the market did not get the relevant news quickly or clearly. So, the information that flow among traders was not readily available for the investors at the same level and time. Ultimately, the Saudi stock market is described as a weak-form market (inefficient).Keywords: Unanticipated political events, the stock market, expected returns, abnormal returns, cumulative returns, event study methodologyAbstract: This study aims to identify the effect of unexpected political-events on Saudi stock market returns based on the efficient market hypothesis (EMH) assumptions.  The disappearance of the Saudi journalist Jamal Khashoggi in Turkey is the political event has been determined in this study.  The data collected from ten companies traded in the Saudi stock market which accounted for more than 62 percent of the total market capitalization. However, this paper applied the Event Study Methodology. The results showed that the Saudi stock market initially reacted to the event and tried to absorb the information received but could not correct itself in most of the window event period. It seems that the market did not get the relevant news quickly or clearly. So, the information that flow among traders was not readily available for the investors at the same level and time. Ultimately, the Saudi stock market is described as a weak-form market (inefficient).Keywords: Unanticipated political events, the stock market, expected returns, abnormal returns, cumulative returns, event study methodology.